83.4k views
2 votes
What is the equation for the graph below?

A y = − (x − 3)2 + 1
B y = − (x + 3)2 + 1
C y = (x − 3)2 − 1
D y = (x + 3)2 − 1

What is the equation for the graph below? A y = − (x − 3)2 + 1 B y = − (x + 3)2 + 1 C-example-1
User Sivakanesh
by
5.6k points

2 Answers

2 votes

For these type of questions I suggest that you get PhotoStudy.... it would really help you out and explain to you

User Techloverr
by
5.9k points
4 votes

Answer:

D

Explanation:

Lets start by figuring out the vertex. From looking at the picture, you can tell that the vertex (the place where the line thingy stops going down and starts going up) is (-3 , -1).

Now, these equations are set up like this: y2 = h*(x2 - x1) + y1

(-3 , -1) is the same thing as saying (x1 , y1)

So, this rules out A, B, and C

Therefore, your answer is D! :D

User MasterMastic
by
5.9k points